Nuclear Malaysia's Dr. Norimah lectures to first year industrial chemistry students - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Safriza, Baharuddin; Muhammad Najib, Muhammad Nor; Noor Azhar, Abd. Rasid (Penerbit UMP, 2009)
Dr. Norimah Yusof became guest lecturer in their Industrial and Laboratory Safety class(BSKll62).